Risk Factors Leading to Meconium Aspiration Syndrome in Meconium-Stained Amniotic Fluid - Karim, Rukhsana; Akhtar, Robina; Kishwar, Nasreen; Ali, Sadia; Imran, Fatima; Begum, Shamshad; Azim, Tayyaba (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study aimed to find out the risk factors leading to meconium aspiration syndrome in patients having meconium-stained amniotic fluid. METHODOLOGY This comparative study was conducted in the department of Obstetrics and Gynaecology at Hayatabad Medical Complex from January 2022- June 2022. All patients admitted to the labour ward with the diagnosis of meconium-stained liquor (MSL) were included in the study through a convenient sampling technique. Patients were divided into two groups, group 1 having only meconium-stained amniotic fluid (MSAF) without meconium aspiration syndrome while group 2 having babies with the diagnosis of meconium aspiration syndrome (MAS). Both groups were compared for different risk factors for the development of MAS. Differences in the risk factors between the two groups were analyzed using Pearson’s correlation with a p-value of <0.05 considered significant. SPSS vs 20 was used for statistical analysis. RESULTS 84 patients were included in the study, i.e., 61 in group 1 and 23 in group 2. The mean age of the patients was 25± 3.45. The frequency of meconium-stained amniotic fluid was 3.83%. Meconium aspiration syndrome developed in 23 babies out of 84 MSAF deliveries (27.38%). Low APGAR score (< 0.00), patients handled outside the hospital (<0.001) and prolonged second stage (0.003) were significant risk factors for the development of MAS. CONCLUSION In the prolonged second stage, patients handled outside the hospital by unauthorized personnel and low APGAR score at birth were statistically significant risk factors for developing meconium aspiration syndrome.